Relationship of Edoxaban Plasma Concentration and Blood Coagulation in Healthy Volunteers Using Standard Laboratory Tests and Viscoelastic Analysis - Havrdova Martina; Saari Teijo I; Jalonen Jouko; Peltoniemi Marko; Kurkela Mika; Vahlberg Tero; Tienhaara Anri; Backman Janne T; Olkkola Klaus T; Schramko Alexey (WILEY, 2022)
The capability of viscoelastic measurement parameters to screen anticoagulation activity of edoxaban in relation to its plasma concentrations was evaluated in 15 healthy male volunteers. Blood samples were drawn before the oral administration of edoxaban 60 mg and 2, 4, 6, 8, and 24 hours after administration. At each time, standard coagulation tests were performed, blood viscoelastic properties were measured with a thromboelastometry device ROTEM delta analyzer (Instrumentation Laboratory, Werfen, Barcelona, Spain), and edoxaban plasma concentrations were measured. Our primary interest was the possible correlation between edoxaban plasma concentrations and values for ROTEM ExTEM, and FibTEM. We also studied the correlation of edoxaban plasma concentrations with the results of standard coagulation tests. We saw the effect of a single dose of edoxaban most clearly in clotting time (CT) of ROTEM ExTEM and FibTEM. Changes in these parameters correlated significantly with edoxaban plasma concentrations up to 6 hours from the ingestion of the drug. Activated partial thromboplastin time, prothrombin time, and anti-factor Xa were also affected. Peak changes were observed 2 and 4 hours after administration of edoxaban. The changes were mostly reversed after 8 hours. In conclusion, ROTEM CT correlates significantly with edoxaban plasma concentrations and can be used to estimate the effect of edoxaban. ROTEM should be considered as part of the assessment of coagulation, with the big advantage of being readily available on site.